2022
DOI: 10.1021/acs.energyfuels.2c02681
|View full text |Cite
|
Sign up to set email alerts
|

High-Energy-Density Asymmetric Supercapacitor Based on Layered-Double-Hydroxide-Derived CoNi2S4 and Eco-friendly Biomass-Derived Activated Carbon

Abstract: Current work presents a high-performance asymmetric supercapacitor (ASC) using nanostructured cobalt nickel sulfide (CoNi2S4) derived via African marigold flower-like layered double hydroxide (CoNi-LDH) as a cathode and Manihot esculenta-derived activated carbon (MAC) synthesized from oxygen-rich hydrochar as an anode. Optimization for LDH precursors with different times of synthesis was carried out, and best performed CoNi-LDH-12 displayed a specific capacitance of 928 F/g at 1 A/g in a three-electrode system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 50 publications
(85 reference statements)
0
18
0
Order By: Relevance
“…The electrochemical performance of NiMX- and EMAC-700-based asymmetric supercapacitors is higher in comparison to that of recently reported MXene-based asymmetric supercapacitors as shown in Table . In all these reports, the poor performance could be ascribed to the (i) instability of MXene (i.e., Ti-, V-, and Nb-based MXene), (ii) incompatibility in the selection of the cathode and anode, and (iii) electrocatalytic activity of electrode materials. , By resolving this, we have demonstrated a highly stable nickel-based MXene and activated carbon-based supercapacitor with a 47.6 W h/kg energy density with outstanding stability representing an ideal combination for an asymmetric supercapacitor.…”
Section: Results and Discussionmentioning
confidence: 94%
“…The electrochemical performance of NiMX- and EMAC-700-based asymmetric supercapacitors is higher in comparison to that of recently reported MXene-based asymmetric supercapacitors as shown in Table . In all these reports, the poor performance could be ascribed to the (i) instability of MXene (i.e., Ti-, V-, and Nb-based MXene), (ii) incompatibility in the selection of the cathode and anode, and (iii) electrocatalytic activity of electrode materials. , By resolving this, we have demonstrated a highly stable nickel-based MXene and activated carbon-based supercapacitor with a 47.6 W h/kg energy density with outstanding stability representing an ideal combination for an asymmetric supercapacitor.…”
Section: Results and Discussionmentioning
confidence: 94%
“…The variation of diffusion charge contributions with scan rate shows that the diffusion contribution of PP-800/PANI is significantly higher. This is because PANI improves the polarity of the material and also facilitates a short conduction transport route, which in turn enhances the diffusion contribution and hence results in a high performance. …”
Section: Resultsmentioning
confidence: 99%
“…The influence of the aforementioned elements is what causes the Ti 3 C 2 T x -MXene/NiVAl-LDH in this article to demonstrate its exceptional performance when compared with the recently reported similar electrodes, as shown in Table S2 (ESI †). 1,23,28,34,[54][55][56][57][58][59] After it was shown that Ti 3 C 2 T x -MXene/NiVAl-LDH performed remarkably well as the positive electrode material for supercapacitors, a hybrid supercapacitor device was built using these materials: activated carbon (AC) as the negative electrode, 1 M KOH as the electrolyte, and the positive electrode as Ti 3 C 2 T x -MXene/NiVAl-LDH. In order to determine the mass ratio of positive and negative electrodes, cyclic voltammetry (CV) and constant current charge-discharge (GCD) tests were conducted on AC in advance (Fig.…”
Section: Resultsmentioning
confidence: 99%